Phytoconstituents and antidermatophytic activity of crude extracts of Senna occidentalis - Husseini, H. A.; Olonitola, O.S.; Aliyu, M. S. (UMYU Journal of Microbiology Research, 2023)
Dermatophytes are one of the major aetiologic agents of cutaneous mycoses Senna occidentalis is among the plants used in traditional herbal medicine in treating fungal skin infections and it is shown from literature to contain phytochemicals which are attributed to its antidermatophytic activity. This work is aimed at determining the Phytoconstituents and antidermatophytic activity of  leaves and seeds crude extracts of the Senna occidentalis plant . The study is a qualitative study that determines the phytoconstituents and  antidermatophytic activity of the plant extracts on some clinical dermatophyte isolates. The plant  parts were sampled and were used to obtain aqueous and n-hexane extracts using distilled water and n-hexane as extracting solvents respectively. Phytochemical analysis was done on the extracts to  determine the presence of secondary metabolites. The antidermatophytic activity of the extracts on clinical dermatophytes isolates was determined using poisoned food technique. Aqueous extraction gave higher percentage extraction yield than n-hexane extract . All extracts contain secondary metabolites and the extracts showed varying degree of percentage growth inhibition on the isolates. Phytochemical screening of the leaves and seeds extracts of Senna occidentalis revealed the presence of alkaloids, saponins, tannins and other phytoconstituents. The Senna occidentalis leaves and seeds extracts showed growth inhibition percentage (I) ranging between 9% to 39.8% for n-hexane leaf extract,1.3%  to 52.6% for aqueous leaf extract,2.6% to 57.2% for n-hexane seed extract and 12.8% to 61.1% for aqueous seed extract. Senna occidentalis leaves and seeds extract have shown varying potential in inhibiting dermatophyte growth with no  extract having 100% inhibition  percentage on all the tested dermatophytes.